Sex Differences in Adipose Tissue CD8+ T Cells and Regulatory T Cells in Middle-Aged Mice - Ahnstedt, Hilda; Roy-O’Reilly, Meaghan; Spychala, Monica S.; Mobley, Alexis S.; Bravo-Alegria, Javiera; Chauhan, Anjali; Aronowski, Jaroslaw; Marrelli, Sean P.; McCullough, Louise D. (Frontiers in Immunology, 2018)
The prevalence of cardiovascular disease has increased among middle-aged women in the United States, yet has declined in middle-aged men. In experimental stroke, middle-aged females have larger strokes and greater inflammation than age-matched males or younger females. The mechanism underlying this shift from an “ischemia-protected” to an “ischemia-sensitive” phenotype in aging females is unknown. One potential factor is an age-related increase in systemic factors that induce inflammation. Increased abdominal fat deposition is seen in women during middle age. Adipose tissue plays a key role in obesity-induced systemic inflammation, including increased pro-inflammatory cytokines. We hypothesized that age and sex differences in adipose immune cells promote an augmented pro-inflammatory milieu in middle-aged females driven by a balance shift between pro-inflammatory and anti-inflammatory T cells. Abdominal adipose tissue immune cells from young (3–4 months) and middle-aged (15–16 months) male and female C57BL/6J mice were analyzed by flow cytometry. Plasma triglyceride (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) levels were determined with colorimetric assays. Middle-aged mice had higher adipose tissue mass compared to young mice. Lipid profiling showed no sex differences in TG and LDL, but middle-aged females had lower HDL (0.84 ± 0.07 μg/μl) than middle-aged males (1.35 ± 0.06 μg/μl). Flow cytometry data demonstrated an age-associated increase in adipose tissue CD8+ T cells that was augmented by female sex, with middle-aged females having a higher percentage of CD8+ cells (34.4 ± 3.2% of CD3+ T cells) than middle-aged males (24.4 ± 2.2%). This increase in CD8+ T-cell proportion was adipose tissue-specific, as this change was not observed in blood. Middle-aged females had higher numbers of activated (CD69+) CD8+ T cells than males. In addition, female CD8+ T cells produced higher levels of IFN-γ, TNF-α, and granzyme B ex vivo, and females had higher adipose levels of IFN-γ, RANTES and MIP-1β than middle-aged males. In parallel, females had lower levels of regulatory T cells (Tregs), an anti-inflammatory T-cell subtype, compared to age-matched males. In conclusion, middle-aged females have a detrimental combination of elevated pro-inflammatory T cells and decreased anti-inflammatory Tregs in adipose tissue, which may promote a pro-inflammatory milieu and contribute to increased cardiovascular disease burden in aging females.